ON THE NEED TO STUDY KAZAKH-KARAKALPAK RELATIONS - B.N. Tajetdinova (Journals Park Publishing, 2022)
The article covers the views on the relations of the Karakalpak-Kazakh peoples. For the purpose of covering the topic of the article, works of Russian and European scientists were used.
Keywords: Ural region; Karakalpakstan; Kazakh, cultura, ethno-cultural processes